STUDENTS’ SPEAKING ANXIETY OF ENGLISH FOREIGN LANGUAGE (EFL) CLASS AT THE ELEVENTH GRADE OF SMA ALFAQIHIL MUQADDAM KUBU RAYA - Nizarrahmadi; Abdul Mu’thi; Yassin; Muhammad Sood (Pengelola Jurnal Politeknik Negeri Ketapang, 2026)
Vocabulary plays a fundamental role in English language learning as it supports the development of listening, speaking, reading, and writing skills. However, many students still experience difficulties in mastering vocabulary, which affects their motivation and interest in learning. This study aims to examine students’ interest in learning English vocabulary through Live Worksheets and to identify factors influencing their engagement. The research was conducted at SMA Alfaqih Muqaddam Kubu Raya and involved ninth-grade students. A descriptive qualitative approach was employed, with data collected through observations, interviews, and field notes. The findings show that most students (80%) demonstrated a high level of interest in learning vocabulary using Live Worksheets. Interactive features, ease of access, immediate feedback, and attractive visual design contributed to increased student motivation and participation. Interview results further indicate that students perceived Live Worksheets as enjoyable, easy to use, and effective in supporting vocabulary mastery. Students’ interest was influenced by internal factors such as health, cognitive ability, attention, talent, and learning readiness, as well as external factors including family support and the school environment. Overall, Live Worksheets are an effective digital learning medium that enhances student engagement and supports interactive vocabulary instruction.